Sustentabilidade e patrimônio cultural urbano: indicadores - Bernardo Nogueira Capute (2011)
This study displays the challenges in using sustainable indicators in the urban environmental heritage. The decade of 1960 was marked by contestations in diverse parts of the globe, by the magnifying of the heritage concept and by the increase of the ecological conscience. It is presented a historical review on the main resultant recommendations of conferences and meeting concerning the preservation of the human environment and the protection of the world-wide, cultural and natural patrimony of the humanity since 1972. The little relationship between these two fields of research throughout the twenty years that had followed shows itself as a hindrance to the creation and the use of systems of indicators that measure the cultural sustainability. However, only after the United Nations Conference on Environment and Development, in 1992, there was the approach of three fields: the heritage preservation, the territory planning and the environmental preservation. The concept of sustainability, sustainable development and the magnifying of the heritage concept are challenging for the involved managers and communities with these processes of environmental preservation and the cultural heritage protection. Beyond the physical characteristics of its corporeal properties, the cultural identity of the peoples and its values are the resources to be culturally sustained to the future generations, but to measure these historical and cultural elements is a little common task, because they involve value judgments. Preserving this heritage through a participative management that involves specialists, authorities and communities means improving the quality of life of the cities. For this, inside of the matrix of the quality of life, it must be used indicators that evaluate conditions, phenomena and trends and that they are informative, comparative and accessible to the responsible ones for the taking of decisions. Constructing and using indicators or systems of indicators that add information on the different dimensions of the sustainability and its relations of simplified and holistic form without any data are masked are basic to have a notion of the situation as a whole. The study of presented case shows itself as an attempt of creation of an index of identification with the heritage through subjective social indicators, whose main guidelines are the quality of life, the sustainability and the urban environmental heritage. The data on the physical and social conditions of the city of Cataguases had been gotten by one survey so that the interest aspects were treated at great length. If the effectiveness of the politics of preservation of the cultural heritage depends on the integration of this to the economic, social and environmental policies, its indicators must be associated in efficient way. The understanding of the relationship between the diverse dimensions of the sustainability must be faced as a motivation and not as a hindrance to the creation and use of indicators.